Electrogenerated chemiluminescence logic gate operations based on molecule-responsive organic microwires. Issue 29 (12th July 2017) - Gu, Jianmin; Wu, Jingxiao; Gao, Yahui; Wu, Tianhui; Li, Qing; Li, Aixue; Zheng, Jian-Yao; Wen, Bin; Gao, Faming
Abstract : Electrogenerated chemiluminescence logic gate operations using organic microwires as signal transducers have been developed based on specific ECL reaction mechanisms. Abstract : Complex logic gate operations using organic microwires as signal transducers based on electrogenerated chemiluminescence (ECL) intensity as the optical readout signal have been developed by taking advantage of the unique ECL reaction between organic semiconductor 9, 10-bis(phenylethynyl)anthracene (BPEA) microwires and small molecules. The BPEA microwires, prepared on cleaned-ITO substrate using a simple physical vapor transport (PVT) method, were subsequently used for construction of the ECL sensors. The developed sensor exhibits high ECL efficiency and excellent stability in the presence of co-reactant tripropylamine. Based on the remarkable detection performance of BPEA MWs/TPrA system, the sensors manifested high sensitive ECL response in a wide linear range with low detection limit for the detection of dopamine, proline or methylene blue, which behaves on the basis of molecule-responsive ECL properties based on different ECL reaction mechanisms. Inspired by this, these sensing systems can be utilized to design OR, XOR and INHIBIT logic gates, which would be used for the determination of dopamine, proline and ethylene blue via logic outputs. Importantly, the individual logic gates can be easily brought together through three-input operations to function as integrated logic gates.